The Christchurch Earthquake: Crush Injury, Neuropathic Pain, and Posttraumatic Stress Disorder - Frances Cammack; Edward A. Shipton (Case Reports in Medicine)
On February 22, 2011, an earthquake of magnitude 6.3 struck Christchurch, New Zealand. The peak ground acceleration, a measure of the shaking or intensity of an earthquake, was one of the highest ever recorded worldwide. One hundred and eighty-five people lost their lives; many others were injured. Two cases both involving young women are presented; they sustained crush injuries to limbs after being trapped by falling debris and went on to develop severe neuropathic pain. This report examines the mechanisms of neuropathic pain in the setting of crush injury, the treatment modalities, and the association between chronic pain and posttraumatic stress disorder. These case reports highlight the fact that crush injury is relatively common during major earthquakes and that neuropathic pain is an important sequel of this. Post-traumatic stress disorder is common in earthquake survivors with a recognised association with chronic pain. Pain-related disability may increase as well. Issues such as chronic pain and physical disability should not be overlooked as attention focuses on disaster management and the treatment of life-threatening injuries.